Nutrition Status of Children, Teenagers, and Adults From National Health and Nutrition Surveys in Mexico From 2006 to 2020 - Shamah-Levy, Teresa; Cuevas-Nasu, Lucia; Romero-Martínez, Martín; Gómez-Humaran, Ignacio Méndez; Ávila-Arcos, Marco Antonio; Rivera, Juan A. (Frontiers in Nutrition, 2021)
Background: Population-level health and nutrition surveys provide critical anthropometric data used to monitor trends of the prevalence of under nutrition and overweight in children under 5 years old, and overweight and obesity in the population over 5 years of age. Objective: Analyze the children malnutrition and overweight and obesity in children, teenagers and adults through the National Health and Nutrition Surveys information available from public databases. Materials and Methods: Comparable anthropometric data was gathered by five Mexican National Health and Nutrition Surveys (in Spanish, ENSANUT). In pre-school-age children, under nutrition status was identified through underweight (Z-score below −2 in weight-for-age), stunting (chronic malnutrition) (Z-score below −2 for length/height-for-age), or wasting (Z-score below −2, for weight-for-length/height); overweight status was defined as a body mass index (BMI, kg/m2) for age over +2. For school-age children and adolescents, a Z-score BMI between +1 and +2 deviations was defined as overweight, and between +2 and +5.5 as obesity. In adults (≥20 years of age), overweight status was classified as a BMI between 25.0 and 29.9, and obesity as ≥30. Results: The anthropometric data presented derives from the databases of five survey years of the Mexican National Health and Nutrition Survey: 2006, 2012, 2016, 2018, and 2020. They include a total of 210,915 subjects with complete anthropometric data (weight, length/height) distributed on five survey moments; subjects were categorized by age group: pre-school-age children (n = 25,968), school-age children (n = 42,255), adolescents (n = 39,275), and adults (n = 103,417). Prevalence of malnutrition by indicator was calculated: in pre-school-age children: low height- and weight-for-age, low weight-for-height, and overweight; and in school-age children, adolescents, and adults, the indicators calculated were overweight and obesity. Conclusions: Results demonstrate the importance of maintaining systematic, reliable, and timely national anthropometric data in the population, in order to detect and track trends and to form the basis of nutrition-related public policy.